2012
DOI: 10.1088/0031-9155/57/24/8297
|View full text |Cite
|
Sign up to set email alerts
|

Dose-distance metric that predicts late rectal bleeding in patients receiving radical prostate external-beam radiotherapy

Abstract: The relationship between rectal dose distribution and the incidence of late rectal complications following external-beam radiotherapy has been previously studied using dose-volume histograms or dose-surface histograms. However, they do not account for the spatial dose distribution. This study proposes a metric based on both surface dose and distance that can predict the incidence of rectal bleeding in prostate cancer patients treated with radical radiotherapy. One hundred and forty-four patients treated with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…For instance, Buettner et al presented a late rectal toxicity method based on the parameterized representation of the 3D rectal dose [ 39 ]. Lee et al proposed a metric based on both surface dose and distance to predict incidence of the rectal bleeding in prostate cancer patients treated with radical radiotherapy [ 40 ]. Drean et al identified rectal subregions at risk of rectal bleeding by performing voxel-wise analysis on the rectal dose distribution [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Buettner et al presented a late rectal toxicity method based on the parameterized representation of the 3D rectal dose [ 39 ]. Lee et al proposed a metric based on both surface dose and distance to predict incidence of the rectal bleeding in prostate cancer patients treated with radical radiotherapy [ 40 ]. Drean et al identified rectal subregions at risk of rectal bleeding by performing voxel-wise analysis on the rectal dose distribution [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have studied the risk of rectal complications from radiotherapy in terms of dose-volume histogram (DVH) data [1]. However, a limitation of a DVH is that the spatial distribution of dose is disregarded; therefore, several studies have recently considered spatial features [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] of the three-dimensional (3D) dose distribution in order to improve the performance of predictive models. The development of ever more elaborate normal-tissue complication probability (NTCP) models is driven by the concern that a poor characterization of the dose-response relationship may unnecessarily limit the effectiveness of the treatment; a simplistic NTCP model could imply conservative dose-volume constraints to the organs-at-risk (OAR), or cause avoidable suffering through a suboptimal distribution of the dose to OAR for a given tumor dose (e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively weak associations may be explained by at least two key factors: (1) inter-fractional differences in rectal filling status, which make the planned dose not representative of the accumulated dose [10]; and (2) disregarding of spatial information. Rectal dose surface maps (DSMs) have been suggested as a solution to account for spatial patterns in associations between dose distributions and GI toxicity, potentially improving doseresponse relationships [11][12][13][14][15]. Statistical simulations of motion-inclusive accumulated doses have showed potentially stronger associations to morbidity risk than the planned doses [16][17][18].…”
Section: Introductionmentioning
confidence: 99%